Respuestas

2013-05-10T02:43:26+02:00

4(x-1)+3(x+5)=2x+41---------------------------------------------

 7 x+11 = 2 x+41

5 x=30
x=30/5
x=6

 

 

5x-11+2(2x+3)=2x+9-----------------------------------------

 9 x-5 = 2 x+9

7 x=14
x=14/7 x = 2

 

 

 

5(7+4x)-15-8x=92

4 (3 x+5) = 92 12 x+20 = 92 12 x = 92-20 12 x = 72
x=72/12 x = 6
2013-05-10T03:36:53+02:00

4(x-1)+3(x+5)=2x+41

4x-4+3x+15=2x+41

7x+11=2x+41

7x-2x=41-11

5x=30

x=30/5

x=6

 

 

5x-11+4x+6=2x+9

9x-5=2x+9

9x-2x=9+5

7x=14

x=14/7

x=2

 

5(7+4x)-15-8x=92

35+20x-15-8x=92

12x+20=92

12x=92-20

12x=72

x=72/12

x=6